2009
DOI: 10.1111/j.1540-6040.2009.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Suburban Neighborhood Poverty in U.S. Metropolitan Areas in 2000

Abstract: Suburban areas have become more diverse and stratified in the United States, with a particularly striking increase in poverty, challenging theories that conceptualize poverty predominantly as a central city phenomenon. Little scholarly work has examined suburban poverty, however, and the small existing literature focuses primarily on inner-ring suburbs in the Northeast and Midwest and relies too much on the concentric zone model of metropolitan development. We use Census 2000 summary data to examine the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…Several studies have found that African Americans and some immigrant ethnic groups living in suburbs can experience poverty and dilapidation comparable to their counterparts in central cities (Hanlon, 2010; Holliday and Dwyer, 2009; Logan et al, 2002; Patillo-McCoy, 1999). The work of Hanlon (2010), in particular, stresses that suburban communities that closely border cities, so called ‘inner ring’ suburbs, are notable for poverty and high minority concentrations, more similar in nature to central cities than outer-ring suburbs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several studies have found that African Americans and some immigrant ethnic groups living in suburbs can experience poverty and dilapidation comparable to their counterparts in central cities (Hanlon, 2010; Holliday and Dwyer, 2009; Logan et al, 2002; Patillo-McCoy, 1999). The work of Hanlon (2010), in particular, stresses that suburban communities that closely border cities, so called ‘inner ring’ suburbs, are notable for poverty and high minority concentrations, more similar in nature to central cities than outer-ring suburbs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Latino density, is strongly correlated with area-level socioeconomic deprivation, quality and disorder, such that the independent effects and contributing mechanisms of each are difficult to disentangle (Bécares 2014, Hong, Zhang & Walton 2014, Sampson, Raudenbush & Earls 1997). Evenness measures, however, are less correlated with socioeconomic deprivation, especially among measures of Latino segregation (Denton 1994, Holliday, Dwyer 2009, Jargowsky 1997, Vélez, Martin & Mendez 2009). The effects of Latino density and Latino segregation are thought to effect SRH through similar mechanisms yet the effects of Latino segregation are more easily separated from potential confounders than are those of Latino density, such that ‘formal’ segregation measures more clearly describe effects on SRH (White, Borrell 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the poor have suburbanized (Berube & Frey, 2002;Cooke, 2010;Cooke & Marchant, 2006;Holliday & Dwyer, 2009;Jargowsky, 2003;Kingsley & Pettit, 2003). In 2000, 49% of all poor people resided in the suburbs, up from 46% in 1990 (Berube & Frey, 2002).…”
Section: Suburbanization and Spatial Mismatchmentioning
confidence: 98%